A tecnologia assistiva digital na alfabetização de crianças surdas - Barbosa, Josilene Souza Lima (2011)
The present learning has porpose examime the contribuition about attending digital tecnology on deaf children alfabetization process. These children face alot of difficults in this scholarization fase it´s just to scarcity of methodologies and appropriate resort to teaching. It has been adopt to this search the studying methold with qualitative boarding case, it´s having as empiric field a public school João Cardoso do Nascimento Júnior in Aracaju and as gothering of instrument spontoneous observation, systematic and participing; interviews with the informatic has teachers and as classroom too. Seven deaf students were chosen with age between ten and twelve years of which three show associated limitation, how: autism. Intelectual deficience and dificit diseppointment of great activities/attention. So seven af subject were chosen four of all were only deaf to given analysis.The seaech is esbilished on partner historic proposed by vygotsky, and the kinds were analysed with base on three development zones descripted for this theoric as subsidiary theoric, were utilized vygotsky analysis (1989), Souza (2005), Souza(2007), Galvão Filho (2009).Schneider(2002), Bersch (2007), Quadros (2006), including others the facts evidenced that the resort about digital assistive tecnology descried new perspectives and possibilites on these children learning process. Whatsoever these resources. When following of a criterous planning can be torning an important instrument to a mediation knowledge and so elevating own valuation and awaking the interrest af students to new learning.